Customer satisfaction in the personal grooming service industry in Singapore. - Lim, Hwee Hong. (2008)
This paper attempts to measure the customer satisfaction level in the personal grooming service industry in Singapore. The focus is on the level of service quality in three segments, namely the skincare service segment, the manicure/pedicure service segment and the spa service segment.